Metabolomic adjustments in the orchid mycorrhizal fungus Tulasnella calospora during symbiosis with Serapias vomeracea. Issue 6 (13th August 2020) - Ghirardo, Andrea; Fochi, Valeria; Lange, Birgit; Witting, Michael; Schnitzler, Jörg‐Peter; Perotto, Silvia; Balestrini, Raffaella
Summary: All orchids rely on mycorrhizal fungi for organic carbon, at least during early development. In fact, orchid seed germination leads to the formation of a protocorm, a heterotrophic postembryonic structure colonized by intracellular fungal coils, thought to be the site of nutrient transfer. The molecular mechanisms underlying mycorrhizal interactions and metabolic changes induced by this symbiosis in both partners remain mostly unknown. We studied plant–fungus interactions in the mycorrhizal association between the Mediterranean orchid Serapias vomeracea and the basidiomycete Tulasnella calospora using nontargeted metabolomics. Plant and fungal metabolomes obtained from symbiotic structures were compared with those obtained under asymbiotic conditions. Symbiosis induced substantial metabolomic alterations in both partners. In particular, structural and signaling lipid compounds increased markedly in the external fungal mycelium growing near the symbiotic protocorms, whereas chito‐oligosaccharides were identified uniquely in symbiotic protocorms. This work represents the first description of metabolic changes occurring in orchid mycorrhiza. These results – combined with previous transcriptomic data – provide novel insights on the mechanisms underlying the orchid mycorrhizal association and open intriguing questions on the role of fungal lipids in this symbiosis.